Komunikasi dan Akulturasi: Studi Fenomenologi pada Masyarakat Lokal dan Muslim di Perbatasan Indonesia-Malaysia - Bob Andrian (IAIN Palangka Raya, 2020)
This study attempted to analyze the process of communication and socio-cultural acculturation, especially local society with Muslims at the border. This research was qualitative using a naturalistic paradigm, with a phenomenological approach. Data were obtained through three ways, namely observation, interviews and documentation. The research method was a case study. The analysis revealed that, first, acculturation in border society occured because there were five aspects affecting it such as increasing population, increasing levels of education, easy and free access to economy, attractions and socio-cultural heterogeneity at the border. The existence of these factors contributed greatly to the reconstruction of the social order of border society. The process of dialectics and communication between cultures of local society and Muslims was bound to make the acculturation process between the two or vice versa. Based on the field findings, there were at least two forms of acculturation process, namely culutural cover and overt cultural. Second, the form of acculturation had two major influences on the local society in particular and the migrant society in general both negative and positive influences. Negative influences included the declining local culture, which began to diminish and traditional lifestyles beginning to change more modern. Meanwhile, positive influences included more practical methods of farming to support local society life, ways of thinking that were more advanced and developing, and more modern lifestyles. As for the acculturation process, it emerged several cultures. Among of them were to create new cultures, such as farming culture, lifestyle, and knowledge. There were also those who maintained the existence of each cultural substance such as language, values and innate norms inherent in the element of origin of culture. Also, it eliminated the culture existed between the two cultures, both the local people culture and the newcomers culture including the way of life from the traditional farming patterns to being more modern.Keyword : Acculturation, Communication, Border Society